Online forums, audience participation and modes of political discussion: readers’ comments on the Brazilian presidential election as a case study (Communication & Society, 2013)
The Internet has created new “dialogical spaces”1 where issues of common concern can be discussed, serving to democratize the public sphere. However, some scholars express doubts about the quality of the debates that occur in the online environment, pointing out the fragmentation, the incivility or even the anonymity as major problems that may undermine the expansion of the online public sphere.As a potential deliberative section and a civic forum, readers’ comments in newspapers’ websites constitute a locus for public debate and ideas exchange provided by the mainstream media. As a case study, this article intends to assess the quality of audience participation in online news sites, by analysing the readers’ comments in the news about the Brazilian presidential campaign (September-November 2010) in the online versions of two Portuguese newspapers.